Ekstraksi Ciri Menggunakan Metode Transformasi Warna YCBCR Untuk Klasifikasi Kulit Manusia - Enny Indasyah; Elsen Ronando (Jurnal Mantik Penusa, 2017)
Skin can be used as information for example the detection process for detection of human, face detection and face tracking, which includes the introduction of the hand tracking, hand position and movement (gesture), medical diagnostics such as detection of skin cancer, and others . Detection of skin affected by various factors such as illumination, background, camera characteristics, and ethnicity. In its application, the classification types of skin color are processed with OpenCV library. In this study, using YCbCr color model. For further performed to skin segmentation separate between skin pixels and not skin that refers to range of skin. After that is done the morphology and the average value obtained from YCrCb skin only. After that is done the process of clustering algorithms to divide into 4 clusters of white, yellow, brown and black. The purpose of this research is to apply the YCbCr color transformation method. In this study there were pictures of human faces with different types of skin colors namely white, black, yellow and brown were taken offline from image. Results obtained from these tests the average Cr and Cb, and the clustering results obtained are 4 kinds of skin.